A Rare Corticotroph-Secreting Tumor with Coexisting Prolactin and Growth Hormone Staining Cells. (5th December 2012) - Kannan, Subramanian; Staugaitis, Susan M.; Weil, Robert J.; Hatipoglu, Betul
Abstract : Pituitary adenomas can express and secrete different hormones. Expression of pituitary hormones in nonneoplastic pituitary cells is regulated by different transcription factors. Some pituitary adenomas show plurihormonal expression. The most commonly reported plurihormonal adenomas are composed of somatotrophs, lactotrophs, thyrotrophs and gonadotrophs. Pituitary adenomas composed of both corticotroph and somatolactotroph secreting cells are not common because transcription factors regulating the expression of these hormones are different. We report a rare case of pituitary adenoma with concomitant corticotroph, prolactin, and growth hormone staining cells, review literature on similar cases, and discuss possible biological mechanisms underlying these plurihormonal tumors.